Two definitions of the electric polarizability of a bound system in relativistic quantum theory - Coutinho, F. A B; Nogami, Y.; Tomio, Lauro [UNESP] (American Association of Physics Teachers (AAPT), 1999)
For the electric polarizability of a bound system in relativistic quantum theory, there are two definitions that have appeared in the literature. They differ depending on whether or not the vacuum background is included in the system. A recent confusion in this connection is clarified. © 1999 American Associations of Physics Teachers.